Semi-permanent tattoos in breast radiotherapy (STaBRad) study: a randomised-controlled clinical trial comparing the 'Precision Plus Micropigmentation System' to permanent skin tattoos in radical breast radiotherapy patients. Issue 1 (10th November 2017) - O'Neill, A.; McAleer, S.; McCarty, H.; Clarke, J.; Drake, A.; Hurwitz, J.; Clayton, A.; Shaw, E.; Vennard, H.; Gray, S.; Robinson, J.; Simpson, B.; et al.
Abstract: Introduction and purpose: Accurate and reproducible patient positioning is a critical step in radiotherapy for breast cancer. This has seen the use of permanent skin markings becoming standard practice in many centres. Permanent skin markings may have a negative impact on long-term cosmetic outcome, which may in turn, have psychological implications in terms of body image. The aim of this study was to investigate the feasibility of using a semi-permanent tattooing device for the administration of skin marks for breast radiotherapy set-up. Materials and methods: This was designed as a phase II double-blinded randomised-controlled study comparing our standard permanent tattoos with the Precision Plus Micropigmentation (PPMS) device method. Patients referred for radical breast radiotherapy were eligible for the study. Each study participant had three marks applied using a randomised combination of the standard permanent and PPMS methods and was blinded to the type of each mark. Follow up was at routine appointments until 24 months post radiotherapy. Participants and a blind assessor were invited to score the visibility of each tattoo at each follow-up using a Visual Analogue Scale. Tattoo scores at each time point and change in tattoo scores at 24 months were analysed by a general linear model using the patient as a fixed effect and the type of tattoo (standard or research) as covariate. A simple questionnaire was used to assess radiographer feedback on using the PPMS. Results: In total, 60 patients were recruited to the study, of which 55 were available for follow-up at 24 months. Semi-permanent tattoos were more visible at 24 months than the permanent tattoos. Semi-permanent tattoos demonstrated a greater degree of fade than the permanent tattoos at 24 months (final time point) post completion of radiotherapy. This was not statistically significant, although it was more apparent for the patient scores ( p =0·071) than the blind assessor scores ( p =0·27). No semi-permanent tattoos required re-marking before the end of radiotherapy and no adverse skin reactions were observed. Conclusion: The PPMS presents a safe and feasible alternative to our permanent tattooing method. An extended period of follow-up is required to fully assess the extent of semi-permanent tattoo fade.